Analysis of Problem Based Learning Models to Improve Creative Thinking Ability of Senior High School Students on Momentum and Impulse Topic - I Putu yogi Setia Permana; Parno Parno; Endang Purwaningsih; Marlina Ali (Jurnal Pembelajaran Fisika, 2023)
Schools must have the 4C abilities, notably creative thinking, to keep up with the advancement of science and technology in the 21st century's educational institutions. The ability to think creatively strives to involve activities, analyze, synthesize, generate conjectures, create something new, and utilize the knowledge acquired in practical ways. Some studies show that students' creative thinking skills in momentum and impulse materials are not optimal. One of the factors that cause students' low creative thinking skills is the learning process. This study aims to provide an overview of students' creative aptitudes on momentum and impulse topics. This study used a mixed method with an embedded experimental design. At SMA 1 Menggala in Lampung, this study was carried out. 28 students of class X MIPA 2 involved in the study were taken as samples with a saturated sampling technique. For this study, the students participated in tests and interviews. Of the four essay questions on momentum and impulse that made up the creative thinking ability exam each validity value (0.686) and reliability (0.610) had a high category. A creative mind is characterized by fluency, flexibility, originality, and elaboration. Problem-based learning models can help students' creative thinking skills, according to the findings of research on the subject. According to the results of the investigation, most students have a high level of creativity on the indicator of fluency. The problem-based learning model is successful in enhancing the ability to think creatively and is expected to be applied in further research on different topics.Keywords: Creative Thinking Ability, Problem-Based Learning, Impulse and MomentumDOI: http://dx.doi.org/10.23960/jpf.v11.n1.202304